PTX3 Deficiency Promotes Enhanced Accumulation and Function of CD11c+CD11b+ DCs in a Murine Model of Allergic Inflammation - Balhara, Jyoti; Koussih, Latifa; Mohammed, Ashfaque; Shan, Lianyu; Lamkhioued, Bouchaib; Gounni, Abdelilah S. (Frontiers in Immunology, 2021)
PTX3 is a unique member of the long pentraxins family and plays an indispensable role in regulating the immune system. We previously showed that PTX3 deletion aggravates allergic inflammation via a Th17 -dominant phenotype and enhanced CD4 T cell survival using a murine model of ovalbumin (OVA) induced allergic inflammation. In this study, we identified that upon OVA exposure, increased infiltration of CD11c+CD11b+ dendritic cells (DCs) was observed in the lungs of PTX3-/- mice compared to wild type littermate. Further analysis showed that a short-term OVA exposure led to an increased number of bone marrow common myeloid progenitors (CMP) population concomitantly with increased Ly6Chigh CCR2high monocytes and CD11c+CD11b+ DCs in the lungs. Also, pulmonary CD11c+CD11b+ DCs from OVA-exposed PTX3-/- mice exhibited enhanced expression of maturation markers, chemokines receptors CCR2 and increased OVA uptake and processing compared to wild type controls. Taken together, our data suggest that PTX3 deficiency heightened lung CD11c+CD11b+DC numbers and function, hence exacerbating airway inflammatory response.